MATHEMATICAL MODELLING OF BIOLOGICAL WASTEWATER TREATMENT OF OXIDATION POND - MUHAMMAD, NURUL NADIAH (2020)
Oxidation pond is known as shallow pond designed to treat wastewater through its interaction with sunlight, bacteria and algae. However, water pollution occurs due to harmful substances, including chemicals, with a high concentration of toxic material, thus affecting the water treatment process because bacteria can only degrade the pollutants. Moreover, various studies have used the partial differential equations (PDEs) model for oxidation ponds, but were unable to analyse the stability of the model, including steady-state and bifurcation, which is crucial for evaluating the reliability and significance of the proposed model.